2018
DOI: 10.17116/stomat20189704123
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of paste and suspension with nano-hydroxyapatite on the sensitivity of teeth with gingival recession

Abstract: The purpose of our study was to assess the efficiency of toothpaste 'Intensive strengthening of supersensitive teeth with nano-GAP' INNOVA and the suspension 'Liquid Enamel' INNOVA on the sensitivity of teeth with gingival recession. We examined 40 people aged 20-25 years. Each group consisted of 20 people: 10 women, 10 men. The first group (observations) used the paste and the suspension for 14 days, and the second group (comparisons) cleaned teeth only with a brush without a paste. Schiff aerial test was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…But in present of F reduce the loss of enamel and dentin subsurface hardness Nano-HAP [ 55 ] Whitening Nano-HAP toothpaste has a satisfying post brushing whitening effect and good resistance to mechanical forces. The whitening effect seemed to be concentration-dependent Nano-HAP [ 77 ] Whitening toothpaste containing Nano-HAP provided a high degree of colour change in the short term and did not create significant surface roughness Nano-HAP [ 78 ] Hypersensitivity combination of paste and liquid suspension with Nano-HAP for 14 days effectively reduced the hypersensitivity of the teeth with gingival recession -Nano-HAP 15 wt% [ 79 ] Hypersensitivity The result of a randomized double-blind clinical study showed that Nano-HAP in F-free toothpastes significantly reduced sensitivity to air and touch (P 0.001). -Nano-HAP 2 wt% gel [ 80 ] Hypersensitivity Toothpaste containing 2 % Nano-HAP significantly reduced tooth hypersensitivity - KNO 3 , sodium Na 2 PO 3 F, and Nano-HAP plus antioxidants [ 81 ] Hypersensitivity KNO 3 acts on neuroreceptors, while Na 2 PO 3 F and Nano-HAP affect renal tubule occlusion and show synergy in preventing hypersensitivity.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…But in present of F reduce the loss of enamel and dentin subsurface hardness Nano-HAP [ 55 ] Whitening Nano-HAP toothpaste has a satisfying post brushing whitening effect and good resistance to mechanical forces. The whitening effect seemed to be concentration-dependent Nano-HAP [ 77 ] Whitening toothpaste containing Nano-HAP provided a high degree of colour change in the short term and did not create significant surface roughness Nano-HAP [ 78 ] Hypersensitivity combination of paste and liquid suspension with Nano-HAP for 14 days effectively reduced the hypersensitivity of the teeth with gingival recession -Nano-HAP 15 wt% [ 79 ] Hypersensitivity The result of a randomized double-blind clinical study showed that Nano-HAP in F-free toothpastes significantly reduced sensitivity to air and touch (P 0.001). -Nano-HAP 2 wt% gel [ 80 ] Hypersensitivity Toothpaste containing 2 % Nano-HAP significantly reduced tooth hypersensitivity - KNO 3 , sodium Na 2 PO 3 F, and Nano-HAP plus antioxidants [ 81 ] Hypersensitivity KNO 3 acts on neuroreceptors, while Na 2 PO 3 F and Nano-HAP affect renal tubule occlusion and show synergy in preventing hypersensitivity.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…Details of the studies in this figure are in Table 1 . Other references: Alharith [ 24 ], Browning [ 32 ], Ding [ 36 ], Makeeva [ 51 ], Vano [ 61 , 62 ].…”
Section: Figurementioning
confidence: 99%
“…SEM evaluation of the extracted teeth was performed in compliance with the protocol approved by the Ethics Committee of Sechenov University. [ 11 12 13 14 15 16 17 18 ]…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
“…[ 12 ] Different HAP- and nHAP-containing toothpastes are effective in reducing DH in many studies. [ 13 14 15 16 ] Although many treatment regimens with the use of calcium apatites have been recommended in recent years, there is a paucity of literature on the comparison of various modifications of nHAP. Therefore, the present study aimed to compare the effect of toothpastes containing nano-hydroxyapatite (nHAP), nano-Zn-Mg-hydroxyapatite (nZnMgHAP), and nano-fluoroapatite (nFAP) on DH associated with noncarious cervical lesions.…”
Section: Introductionmentioning
confidence: 99%